IOT Based Intelligent Energy Monitoring of Grid connected Hybrid systems and controlling of Loads using PLC (2024)
Nowadays IOT becoming popularize in all the application especially in the power system network for data monitoring from the Hybrid power distribution system. Because of easy adaptability of IOT technology, it find its place in data monitoring for the remote system and data can also be logged in the cloud server for analysis of the system under surveillance. By having data enabled IOT system, which will make the complete system smarter in terms of monitoring and analysis of the performance of the power distribution network. In these research paper, concept IOT technology for data monitoring of grid connected Hybrid system consist of PV source for the typical educational institute was developed and implemented in the campus. Apart from the data monitoring, controlling of the critical loads connected to this hybrid system was developed using Programmable Logic Controller (PLC). The MyQtt based cloud server was used to store the data pushed from the IOT device and user interactive mobile Application was developed using MIT inventor to monitor the data in the mobile itself, the command from the Mobile app was given to the PLC to control the loads. The energy data from the Multi-function energy meter (MFM) is pushed to PLC through gateway of Raspberry Pi. In this paper, Raspberry PI was used as IOT device and ILC 131 ETH PLC was used to control the loads. Performance of IOT device along with PLC was monitored for 3 months and results obtained were satisfactory.